Islam: a religion of peace or force? an analysis based on the Qur’ an Sunnah and Islams heritage - Ushama, Thameem (Hamdard Foundation Pakistan, 2020)
We establish that Islam is a religion that sustains peace and catalyses universal harmony. This paper offers qualitative content analysis of Muslim Scripture to clarify that peace is integral to Islamic doctrine. Interpretations by reliable exegetes articulate that this is fact from Scripture and Sunnah. We offer views from notable Western scholars who clearly state that Islam is a peaceful religion and was never spread at the point of sword, but rather as a creed without any imposition of fear or fanaticism. The author also explores Islam’s substantial contributions to a sustainable environment of global peace.